2014
DOI: 10.1080/00221309.2014.938721
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Individualism and Collectivism Predict Ratings of Virtual Cities’ Liveability and Environmental Quality

Abstract: The present research investigated individual differences in individualism and collectivism as predictors of people's reactions to cities. Psychology undergraduate students (N = 148) took virtual guided tours around historical cities. They then evaluated the cities' liveability and environmental quality and completed measures of individualism and collectivism. Mediation analyses showed that people who scored high in self-responsibility (individualism) rated the cities as more liveable because they perceived the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…As we have reported in greater detail in an article in Journal of General Psychology (Rubin;Morrison 2014), the overall analysis of the survey showed that people who reported a strong sense of self-responsibility (individualism) rated the cities as more liveable because they perceived them to be richer and better resourced. In contrast, people who reported a strong commitment to their social groups (collectivism) rated the cities as having a better environmental quality because they perceived them to provide a greater potential for community and social life.…”
Section: The Research Surveymentioning
confidence: 77%
See 2 more Smart Citations
“…As we have reported in greater detail in an article in Journal of General Psychology (Rubin;Morrison 2014), the overall analysis of the survey showed that people who reported a strong sense of self-responsibility (individualism) rated the cities as more liveable because they perceived them to be richer and better resourced. In contrast, people who reported a strong commitment to their social groups (collectivism) rated the cities as having a better environmental quality because they perceived them to provide a greater potential for community and social life.…”
Section: The Research Surveymentioning
confidence: 77%
“…In contrast, people who reported a strong commitment to their social groups (collectivism) rated the cities as having a better environmental quality because they perceived them to provide a greater potential for community and social life. As Rubin and Morrison (2014) explained, individualism and collectivism are cultural orientations towards treating people as individuals or group members respectively (for a review, see Oyserman et al 2002). Individualists tend to be more independent, autonomous, and self-reliant, whereas collectivists tend to be more interdependent and oriented toward their social groups.…”
Section: The Research Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…However, one study has considered the relation between collectivism and city evaluation. Rubin and Morrison (2014) asked 148 Australian undergraduate students to take a virtual walk through one of four 17 th and 19 th century utopian cities (e.g., Campanella's, 1968Campanella's, /1602, City of the Sun). Specifically, participants watched a 2.5minute narrated slideshow of a walk through an uninhabited city from a first-person perspective.…”
Section: Collectivism As a Predictor Of City Identification And City mentioning
confidence: 99%
“…In other words, city identification may mediate (statistically explain) the relation between collectivism and city evaluation. Rubin and Morrison (2014) have shown that collectivism predicts city evaluation. However, as Rubin and Morrison conceded, a key limitation of their research is "that it lacked ecological validity because it involved nonresidents evaluating novel, historical, virtual, and unpopulated cities" (p. 366).…”
Section: Collectivism As a Predictor Of City Identification And City mentioning
confidence: 99%